Peran Kepemimpinan Wali Nagari Perempuan dalam Mewujudkan Sustainable Development Goals (SDGs) Desa di Kabupaten Pesisir Selatan - Fitri, Annisa; Rinawati, Rinawati; Khudri, Nur Saadah; Saputra, Nika; Baguno, Rainal (JESS (Journal of Education on Social Science); Vol 7 No 2 (2023): Civil Society Development in Globalization EraDO - 10.24036/jess.v7i2.535, 2023)
This research was conducted to understand the role of female Nagari Guardians in realizing Sustainable Development Goals (SDGs) in two Nagari in Pesisir Selatan Regency, although since 2007 there has been a law that allows women to become village heads. However, in reality there are still very few women who lead nagari in Minangkabau, as evidenced by the 182 nagari in Pesisir Selatan Regency, there are only 2 female Nagari Wali. The research methodology used was qualitative using in-depth interview techniques, observation and document analysis. The results of the research showed that female Nagari Wali applied situational leadership, adjusting their leadership style and actions based on the situation. Their role in realizing the SDGs includes decision making, village development planning, village data collection to prioritize national programs, and adapting to new habits through the "Independent Village" concept. However, there are several problems faced, including limited resources, lack of awareness and understanding of Wali Nagari regarding the program, limited technology, less than optimal involvement of related parties, and lack of technical and managerial capacity. Social and demographic changes are also factors that influence the implementation of their roles. This research provides an illustration that although female Nagari Mayors have an important role in realizing the SDGs, further steps are still needed to overcome the various problems faced, including capacity building and involvement of related parties